Psicoanálisis de estructuras clínicas y trastorno bipolar - Villalva Motoche, Cristhian Gerardo (My University, 2021)
This article aims to unmask one of the disorders with the greatest diagnostic boom worldwide, from the knowledge of Charcot, and the psychoanalytic perspective of Freud and Lacan, the hysterical personality is recognized as the background of bipolarity, starting from the interaction of the components that structure it and the factors that underlie this type of personality, such as the effect of early sexual experience, the absence and presence of the affective object and its consequences of deficit in the psychic structure of the subject; his psychoanalytic study transcends modern psychology aimed at the ambiguous characterization of disorders, and allows visualizing the subject as a way of being and not as a psychiatric condition.
En el presente artículo se pretende desenmascarar a uno de los trastornos con mayor auge de diagnóstico a nivel mundial, desde los saberes de Charcot, y la perspectiva psicoanalítica de Freud y Lacan, se reconoce a la personalidad histérica como el trasfondo de la bipolaridad, partiendo de la interacción de los componentes que la estructuran y los factores que subyacen a este tipo de personalidad, tales como el efecto de la experiencia sexual temprana, la ausencia y presencia del objeto afectivo y sus consecuencias de déficit en la estructura psíquica del sujeto; su estudio psicoanalítico trasciende a la psicología moderna dirigida a la ambigua caracterización de los trastornos, y permite visualizar al sujeto como un modo de ser y no como una condición psiquiátrica.
Keywords: PSICOANALISIS; HISTERIA; BIPOLARIDAD; PERSONALIDAD HISTERICA